Incorrect Inhaler Technique Compromising Quality of Life of Asthmatic Patients - Hashmi, Anjum; Soomro, Jamil Ahmed; Memon, Afzal; Soomro, Tahira Kasur (Journal of Medicine, 2012)
Introduction: The inhalation route is widely used for the treatment of asthma. It is considered that inadequate inhaler technique is the leading cause of therapy failure. Objective: To determine the proportion of incorrect inhaler use and associated factors in asthmatic patients compromising quality of life. Methodology: It is a cross sectional study conducted at Specialist Chest Clinic Fatima Bhai Hospital Karachi from September 2010 to March 2011. A sample size of 215 was selected by Non-probability purposive sampling technique. Trained health care workers in presence Chest specialist requested patients to demonstrate their inhaler technique and assessed it according to the checklist. If any of the steps was missing or done incorrectly, it was marked as incorrect technique. Information was also collected through a structured questionnaire on socio-demographic variables such as age, gender, education, duration of asthma, duration of inhaler use, and patient education of inhaler technique. Data was entered and analyzed on SPSS-14. Results: There was an inverse relationship between education level and incorrect inhaler technique (p<0.05). Education of inhaler usage provided by doctors was more effective as compared to education provided by nurses (p<0.038). There was no significant relationship between age, sex, duration of asthma, duration of inhaler use, frequency of inhaler use and incorrect inhaler technique. Conclusion: Quality of life of a large percentage of patients is compromised by incorrect inhaler use and education level of patients had significant relationship with incorrect inhaler technique. DOI: http://dx.doi.org/10.3329/jom.v13i1.7980 JOM 2012; 13(1): 16-21